Certified Random: A New Order for Coauthorship - Ray, Debraj; Robson, Arthur (American Economic Review, 2018)
Alphabetical name order is the norm for joint publications in economics. However, alphabetical order confers greater benefits on the first author. In a two-author model, we introduce and study certified random order: the uniform randomization of names made universally known by a commonly understood symbol. Certified random order (i) distributes the gain from first authorship evenly over the alphabet; (ii) allows either author to signal when contributions are extremely unequal; (iii) will invade an environment where alphabetical order is dominant; (iv) is robust to deviations; (v) may be ex ante more efficient than alphabetical order; and (vi) is no more complex than the existing alphabetical system modified by occasional reversal of name order. (JEL A14, Z13)